Design Visual Elements and Brand-Based Equity: Mediating Role of Green Concept - Li, Ying (Frontiers in Psychology, 2022)
Although benefits of design perception have been documented from the perspective of consumers on a large scale, but the perspective of employees has been ignored. This study aims to investigate the impact of design elements on employee-brand-based equity under the mediating role of the green concept. For this purpose, data are collected from the employees of the manufacturing sector and 346 responses are used for an inferential purpose. These data were collected using the survey research method through the convenience sampling technique. Data has been analyzed through Smart PLS by applying the structural equation modeling technique. After assessing the measurement and structural model, the results obtained indicate that design elements of products in the manufacturing industry can influence the perception of employees and it can foster positive behavior among employees in the shape of employee-brand-based equity. The mediating role of the green concept has also been proved. Limitations and future directions are also discussed.